True-3D in Cartography Autostereoscopic and Solid Visualisation of Geodata - Buchroithner, Manfred; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
As corroborated by the never-sagging and even increasing interest within the last decade, the intuitive attraction of "True 3D" in geodata presentation is well worth covering its current status and recent developments in a compendium like the present one. It covers most aspects of (auto-) stereoscopic representation techniques of both topographic and thematic geodata, be they haptic or not. Theory is treated as well as are many fields of concrete applications. Displays for big audiences and special single-user applications are presented, well-established technologies like classical manual fabrication of landscape reliefs contrast with cutting-edge developments
Keywords: Geography; Geographical information systems; Geography; Geographical Information Systems/Cartography.; Earth Sciences, general